THE TRADITION OF THE LAMPU COLOK AHEAD OF EID AL-FITR IN RELIGIOUS VALUES OF THE MALAY SOCIETY IN PEKANBARU - Suroyo, Suroyo (Jurnal Studi Agama dan Masyarakat, 2022)
The Malay community of Pekanbaru Riau still holds traditions that originate from of the values of Islam which is the main religion. The tradition of Lampu Colok is still carried out today with a plug lamp which has its own meaning for the Malay community every 27 Ramadan (night of Lailad al Godt) or often called the night of 7 Likur ahead of Eid al-Fitr. The purpose of this research is to find out the current tradition of the traditional light bulb at the festival in order to survive in the midst of the times with a qualitative approach. The tradition of the lampu colok originated from a story passed down from generation to generation that in the month of Ramadan one must turn on the lamp or there must be lighting. The lampu colok tradition in the Pekanbaru Malay community has various values which include mutual cooperation, economics, social culture, norms and morals, cooperation, beauty, kinship so that it creates a culture of religiosity in the community and can maintain or maintain this lampu colok tradition.